The efficacy of integrated development plan in enhancing service delivery in Lepelle-Nkumpi Local Municipality, Limpopo Province - Makalela, Kagiso Innocent (My University, 2019)
The new democratic government has introduced integrated development planning as a strategy to enhance service delivery at the municipal level. This study intends to investigate the efficacy of IDP in enhancing service delivery in Lepelle-Nkumpi local municipality. This study adopted a normative and evaluative research design. Data was collected using households survey, interviews, observation and literature review. A total of 80 households and 6 key informants participated in the study. The finding revealed that Lepelle-Nkumpi local municipality has been implementing the IDP. The integrated development planning has several importance’s for the municipality in particular to addressing service delivery backlogs, promoting community participation towards determining the needs and priorities as well as improving integration and coordination. However, the implementation of the IDP encountered certain challenges including amongst other poor shortage of resources, incomplete projects poor community participation and political meddling. another finding shows that the municipality has increased the level of services to beneficiary households more especially the delivery of electricity while the provision of water, sanitation and refuse removal are still inadequate. However, due to water and electricity cut-off the households developed some coping strategies. Most households reported their dissatisfaction with the provision of water, sanitation and refuse removal. Regarding involvement of communities in service provision respondents highlighted that municipalities held consultation sessions, IDP forums and ward councillor meetings. However, communities are still dissatisfied about their level of involvement. Despite the overall achievements by the municipality in rendering basic services, there is still a service delivery backlog caused by corrupt practices, shortage of resources, lack of capacity and improper targeting. The finding further shows that the implementation of the IDP has contributed significantly to enhance service delivery in the municipality. It is evident that all the development planning and programmes of the municipality start with the IDP hence the municipality is able to plan and deliver in accordance with the intended needs of the people. The services viii and infrastructural projects implemented through has assisted the municipality to provide basic service such as water, electricity and sanitation. In addition, the municipality has also implemented infrastructure including roads to benefit the community. However, the municipality has not fully achieved the provision of basic services due to poor implementation of the IDP which was caused by lack of capacity, poor community participation and shortage of resources. As a remedy, the study recommend that the municipality should give priority to improve the provision of water, electricity particularly for new settlements, sanitation and refuse removal. It is further recommended that the municipality should pay attention to improve community participation, efficient use of MIG and building its capacity to strengthen the planning and implementation of the IDP.
Thesis (M. Dev. (Planning and Management)) -- University of Limpopo, 2019
Keywords: Development; Integrated Development Plan; Service Delivery; Local Municipality; Municipal government -- South Africa -- Limpopo; Municipal services -- South Africa -- Limpopo; Local government -- South Africa -- Limpopo